ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI KELAPA DALAM DI DESA TINDAKI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Fajrin, Abdul Muis, Moh. (AGROTEKBIS, 2016)
The purpose of this study was to determine the factors that affect the production and income local coconut farming in the village Tindaki Sub DistrictÂ South Parigi Parigi Moutong District, conducted in April to June 2015. Samples taken were 35 respondents from a population of 182 coconut farmers. Sampling used was Method (Simple Random Sampling). The analysis showed that simultaneously (together) factor Total plant (X1), fertilizer salts (X2) and labor (X3) significantly affect coconut production, with the F-count> F-table (60.758 â¥ 2.911) in 95% confidence level. The test results of t-test showed that the partial amount of the plant was highly significant with t count> t-table (9,722â¥2,039), salt fertilizer was highly significant with t count> t-table (7.178 â¥ 2.039) at the rate of 95 %. and labor significantly with t count> t-table (1.914)> t-table (1,696) at the 90% confidence level. Revenue analysis results showed that the average income of coconut farmers in each harvest Rp. 1,703,957/107 trees. / 1.18 ha.